2012
DOI: 10.1007/s00394-012-0350-4
|View full text |Cite
|
Sign up to set email alerts
|

Leg fat might be more protective than arm fat in relation to lipid profile

Abstract: Our data suggest that the region where fat is accumulated might have a differential effect on lipid profile: trunk fat has an adverse effect, leg fat has a protective effect, and arm fat has no effect. The differences observed between upper- and lower-body peripheral fat depots should be further explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 32 publications
3
17
0
Order By: Relevance
“…A study by McLaughlin et al () confirmed that thigh fat behaves as a potential protective factor, as the odds ratios for thigh fat to predict insulin resistance was 0.59, after adjustment of gender and BMI (McLaughlin et al, ). Similar findings were observed in college students, with leg (but not arm) fat linked to reduction of cardiovascular risk factors ( P < 0.05) (Sanchez‐Lopez et al, ). In comparison, Hoyer et al () found that neither mid‐thigh circumference or subcutaneous thigh adipose tissue depot was related to risk of type 2 diabetes diagnosis among Japanese Americans; the odds ratios for both were only 0.9 (Hoyer et al, ) ( P > 0.05).…”
Section: Discussionsupporting
confidence: 75%
“…A study by McLaughlin et al () confirmed that thigh fat behaves as a potential protective factor, as the odds ratios for thigh fat to predict insulin resistance was 0.59, after adjustment of gender and BMI (McLaughlin et al, ). Similar findings were observed in college students, with leg (but not arm) fat linked to reduction of cardiovascular risk factors ( P < 0.05) (Sanchez‐Lopez et al, ). In comparison, Hoyer et al () found that neither mid‐thigh circumference or subcutaneous thigh adipose tissue depot was related to risk of type 2 diabetes diagnosis among Japanese Americans; the odds ratios for both were only 0.9 (Hoyer et al, ) ( P > 0.05).…”
Section: Discussionsupporting
confidence: 75%
“…A few previous studies have examined the independent effects of arm vs leg FM on cardiometabolic risk, but the results have been contradictory 11,50. Although arm FM is regarded as ‘peripheral fat mass’, this is from the upper body and therefore may not exhibit the same protective effects as leg FM.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Furthermore, individuals with less abdominal fat have better metabolic profiles than individuals with comparable BMIs but more abdominal fat. 23,27 Our adolescents who were fit did not demonstrate significant differences in lean body mass between weight groups, yet those with OW/OB exhibited more central adiposity, as measured by both a feasible clinical measure (WC) and a gold standard measure (DXA trunk fat mass) than the adolescents who were normal weight. Furthermore, higher WC and trunk fat mass were positively associated with MSSS and negatively associated with physical fitness in these adolescents across the weight spectrum.…”
Section: Discussionmentioning
confidence: 82%